ORINEL: Zero-Waste Processing of Orange Peel Waste into Natural Anti-Itch Gel for Urticaria Management Via Cold-Glycerin Extraction - Muhammad Hafidz Ghufranuttamam Dharma; Muhammad Raihan Aflatillah; Muhammad Farouq Aji Perkasa; Echa Meizila; Elmira Fatima (Jurnal Impresi Indonesia, 2026)
Urticaria (hives) is a common skin condition causing itchy welts, while orange peel waste from the industry remains an underutilized environmental burden. Orange peels are known to contain bioactive compounds such as flavonoids and limonene, which possess anti-inflammatory and anti-itch properties. This study aimed to develop an effective natural anti-itch gel for urticaria management by converting orange peel waste into a value-added product through a zero-waste approach. Two innovative methods were applied. The first involved a cold-glycerin extraction of fresh orange peels over 14 days to obtain a bioactive filtrate. The second utilized a commercial orange peel extract for efficiency. The extracts were then formulated into a gel using Carbomer 940, neutralized with 1% NaOH, and enhanced with glycerin, Vitamin E, and lavender oil. The result was ORINEL Gel, a 30 mL semi-solid formulation with optimal physical characteristics: a clear yellow appearance, skin-safe pH (5.5-7), and a soft, non-sticky, spreadable texture. The first method fully embodies the zero-waste principle by directly transforming waste into a high-value product. The second method offers production efficiency while maintaining circular economy principles, provided the extract is sourced from waste processing. ORINEL presents a promising, affordable, natural adjuvant therapy for urticaria, simultaneously introducing a sustainable paradigm for organic waste management through upcycling.